2019
DOI: 10.1038/s41598-019-48299-7
|View full text |Cite
|
Sign up to set email alerts
|

E40, a novel microbial protease efficiently detoxifying gluten proteins, for the dietary management of gluten intolerance

Abstract: Gluten proteins are the causative agent of Celiac Disease (CD), a life-long food intolerance characterized by an autoimmune enteropathy. Inadvertent gluten exposure is frequent even in celiac patients complying with a gluten-free diet, and the supplementation of exogenous gluten-digestive enzymes (glutenases) is indeed a promising approach to reduce the risk of dietary gluten boost. Here we describe Endopeptidase 40, a novel glutenase discovered as secreted protein from the soil actinomycete Actinoallomurus A8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
2
38
0
Order By: Relevance
“…Recently, great efforts were made to identify a pharmacological therapy that could be used to replace or support the GFD for treatment of CD patients (103). Currently, several proteolytic enzymes of microbial or plant origins have demonstrated a high efficiency to quickly degrade gluten proteins at very low pH, as occurring in gastric conditions (104)(105)(106)(107). These glutenases, thanks to their efficacy in cleaving the proline-and glutamine-rich gluten sequences are promising drugs to abolish the immunogenic potential of dietary gluten.…”
Section: Gluten Degradation As a Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, great efforts were made to identify a pharmacological therapy that could be used to replace or support the GFD for treatment of CD patients (103). Currently, several proteolytic enzymes of microbial or plant origins have demonstrated a high efficiency to quickly degrade gluten proteins at very low pH, as occurring in gastric conditions (104)(105)(106)(107). These glutenases, thanks to their efficacy in cleaving the proline-and glutamine-rich gluten sequences are promising drugs to abolish the immunogenic potential of dietary gluten.…”
Section: Gluten Degradation As a Treatmentmentioning
confidence: 99%
“…AN-PEP, a prolyl endopeptidase from Aspergillus niger, even though it was not intended to replace a GFD, was effective as a digestive aid protecting against the unintentional intake of gluten (109), or when consuming food which may contain small amounts of gluten, e.g., beer. A recent study demonstrated that the endopeptidase E40 from Actinoallomurus A8 is a fast-acting and strongly efficient glutenase, and thus a candidate as enzyme adjuvant to a GFD for the dietary management of CD (104). Glutenases can also be induced in wheat by germination but the activity is not high enough to be useful as an oral food supplement.…”
Section: Gluten Degradation As a Treatmentmentioning
confidence: 99%
“…Dubé et al (2008) produced in Streptomyces lividans up to 350 mg/L of Streptomyces coelicolor small laccase, a thermostable enzyme decolorizing synthetic dyes that is considered promising for pollutant degradation in urban or industrial wastewaters. Finally, Table 1 and Figure 1A include transferases (6 proteins) for food processing, proteases/peptidases (5) for feed and detergent industries, and phosphatases (2), including a phytase used as supplement for animal nutrition (Carrillo Rincón et al, 2018). Additionally, Torres-Bacete et al (2015) expressed a novel Penicillin V acylase for producing semisynthetic penicillins, whereas Rose et al (2005) a latex clearing protein for bioconversion of rubber wastes.…”
Section: What Are the Recombinant Proteins Produced In Streptomycetes?mentioning
confidence: 99%
“…In Table 1, 21 are the recombinant proteins curing human diseases ( Figure 1A), including those for treating cancer (interleukin, interferon, Tumor Necrosis Factor Alpha-TNFα), cardiovascular pathologies (streptokinase, hirudin), and metabolic or auto-immune disorders (glucagon, phenylalanine ammonia-lyase, tendamistat). Recently, S. lividans TK24 was used for producing an Actinoallomurus A8-sourced glutenase, a promising candidate for oral enzymatic management of gluten toxicity (Cavaletti et al, 2019). Streptomycetes were also used to express 8 'target' proteins, as antigens from Mycobacterium FIGURE 1 | Distribution of the 94 recombinant proteins heterologously produced by streptomycetes and listed in Table 1, according to: use/family of the recombinant protein (A), homologous source (B), heterologous host (C), plasmid (D), and promoter (E) used for heterologous production.…”
Section: What Are the Recombinant Proteins Produced In Streptomycetes?mentioning
confidence: 99%
“…A large number of proteases of microbial, plant and synthetic origin have been proposed to be useful in reducing the content of immunogenic gluten peptides and epitopes (26)(27)(28)(29)(30)(31)(32). Most of these enzymes, such as pseudolysin (IasB) from Pseudomonas aeruginosa (33), nepenthesin from pitcher plants (31,34), endopeptidase 40 from the soil actinomycete Actinoallomurus A8 (32), and an unknown enzyme from human salivary plaques (35), are at early stages of testing but seems to hold great promise. And a handful of these glutenases are already under advanced clinical trials (36).…”
mentioning
confidence: 99%